2017
DOI: 10.1039/c7sc00138j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and selective hydrogenation of amides to alcohols and amines using a well-defined manganese–PNN pincer complex

Abstract: Novel manganese NNP and PNP pincer complexes have been synthesized. The active catalyst allows the efficient hydrogenation of a wide range of amides under relatively mild conditions to afford alcohols and amines in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(96 citation statements)
references
References 104 publications
1
95
0
Order By: Relevance
“…Ther eduction of amides to alcohols and amines (Scheme 8, title reaction) was shown by Beller and coworkers using the imidazole based precatalyst Mn-12. [70] Prakash and co-workers showed that Mn-1 catalyzes the reduction of formamides,w hich are in situ generated from CO 2 ,H 2 ,and amines. [71] Except for precatalyst Fe-2 a,i ntroduced by the group of Milstein, which can hydrogenate activated trifluoroacetamides, [72] all reports of iron-catalyzed amide hydrogenations are based on the Fe complex Fe-25 b [73,74] or its cyclohexyl derivative Fe-25 c. [75] Bernskoetter and co-workers achieved, to date,the lowest reported catalyst loadings for amide reduction (0.07 mol %, formamides) using Fe-4.…”
Section: Hydrogenation Of Amidesmentioning
confidence: 99%
“…Ther eduction of amides to alcohols and amines (Scheme 8, title reaction) was shown by Beller and coworkers using the imidazole based precatalyst Mn-12. [70] Prakash and co-workers showed that Mn-1 catalyzes the reduction of formamides,w hich are in situ generated from CO 2 ,H 2 ,and amines. [71] Except for precatalyst Fe-2 a,i ntroduced by the group of Milstein, which can hydrogenate activated trifluoroacetamides, [72] all reports of iron-catalyzed amide hydrogenations are based on the Fe complex Fe-25 b [73,74] or its cyclohexyl derivative Fe-25 c. [75] Bernskoetter and co-workers achieved, to date,the lowest reported catalyst loadings for amide reduction (0.07 mol %, formamides) using Fe-4.…”
Section: Hydrogenation Of Amidesmentioning
confidence: 99%
“…In contrast to the reductions of different carbonyl compounds presented above, amides are known to be more reluctant to undergo reduction. Very recently, our group published the first selective hydrogenolysis of amides (proceeding via the hemiaminals to afford the corresponding alcohols and amines) by testing three new, air‐stable pincer complexes (Figure ) Whereas complexes 21 and 22 did not show any activity for this transformation, complex 23 promoted hydrogenolysis of secondary and tertiary amides under relatively mild conditions (2–5 mol‐% 23 , 10 mol‐% KO t Bu, 100 °C, 30 bar, cyclohexane, 16 h). The cationic compound 23 has a distorted octahedral geometry in which the PNN ligand has a facial coordination to the manganese centre, as previously also observed for complex 17 .…”
Section: Catalytic Reductionsmentioning
confidence: 99%
“…[5] The potential of manganese catalysts in such redox reactions was exemplified with various type of tridendate ligands, mainly phosphorus and nitrogen atoms. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Interestingly, in the case of hydrogen transfer reaction, using isopropanol as hydrogen donor, Beller has shown that tridentate nitrogen ligand, namely di(picolyl)amine, could promote the reduction of ketones, at 70°C, in 24 h, with a ratio substrate:catalyst of 100:1. [20] Asymmetric reduction of ketones with manganese is far less developed and the two first example were reported by Clarke [21] and Kirchner [22], using related chiral ferrocenyl based tridentate PNN or PNP' ligands.…”
Section: Highlightsmentioning
confidence: 99%